2011
DOI: 10.18632/oncotarget.563
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatase inhibitor, sodium stibogluconate, in combination with interferon (IFN) alpha 2b: phase I trials to identify pharmacodynamic and clinical effects

Abstract: ABSTRACT:Since sodium stibogluconate (SSG) inhibited phosphatases including SHP-1 and augmented anti-tumor actions of IFN-α2b in vitro and in mice, two Phase I trials of SSG/IFN-α2b combination were undertaken to evaluate safety and target inhibition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 53 publications
(86 reference statements)
0
17
0
Order By: Relevance
“…Consequently, antibodies against PD-1 and PD-L1 have entered phase 1 clinical trials, and initial results showing objective tumor regression are highly promising (44,45). More recently, 2 phase 1 trials using the phosphatase inhibitor SSG in combination with IFN-α2b have demonstrated safety and targeted inhibition in cancer patients (24,25). Our findings highlight the critical role of SHP-1 expression among the whole panel of engineered CD8 + T cells.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Consequently, antibodies against PD-1 and PD-L1 have entered phase 1 clinical trials, and initial results showing objective tumor regression are highly promising (44,45). More recently, 2 phase 1 trials using the phosphatase inhibitor SSG in combination with IFN-α2b have demonstrated safety and targeted inhibition in cancer patients (24,25). Our findings highlight the critical role of SHP-1 expression among the whole panel of engineered CD8 + T cells.…”
Section: Discussionmentioning
confidence: 68%
“…Sodium stibogluconate (SSG) is widely used to treat visceral leishmaniasis and was recently identified as an important clinically suitable protein tyrosine phosphatase inhibitor in cancer patients (24,25). Notably, SSG has been shown to selectively inhibit protein tyrosine phosphatases, among which SHP-1 was the most sensitive (26).…”
Section: Engineered T Cells Of Supraphysiological Tcr Affinity Show Ementioning
confidence: 99%
“…Mice in the same group were intravenously injected with either purified MIL containing rhIFNα 2 b at 2×10 6 IU, 1×10 6 IU, or 0.5×10 6 IU, or saline. The animals were kept at room temperature with about 60% humidity and natural light for 12 hours each day, fed with standard solid composite feedstuff, and received tap water ad libitum.…”
Section: Acute-toxicity Testmentioning
confidence: 99%
“…4 IFN has been suggested to play an important role in antivirus, antiproliferative, and immunoregulatory pathways. [5][6][7] Some studies show that IFNα, including IFNα 2 b, is also capable of exerting antitumor effects against HCC, hairy cell leukemia, lymphoma, melanoma, and breast cancer. 3,[8][9][10][11][12][13][14][15][16] However, an extensive clinical trial of IFNα 2 b for HCC was delayed, due to the weak therapeutic effect based on conventional drug-delivery methods.…”
Section: Introductionmentioning
confidence: 99%
“…Although numerous compounds including natural products, small molecules and silencing RNAs are under development [144], efforts are still needed to relate these compounds to clinical application. Among the drugs currently used that have been reported with PTP inhibitory activity, sodium stibogluconate, which was reported able to inhibit SHP-1, SHP-2 and augment antitumor actions of IFN-α2b [145], combined with other anticancer agents, has been explored in clinical trials of solid tumors [146,147]. Despite that PTPs have been revealed as putative oncogenes or tumor suppressor genes, the inhibitors of PTPs applied in the treatment of cancer are rarely reported.…”
Section: • • Jak Inhibitorsmentioning
confidence: 99%